Technology decision-making considerations for coaches: Brain training - Thornton, L. (Olympic & Paralympic Coach, 2015)
This is how an increasing number of my conversations are starting off with coaches. With a rising tide of sport-based apps, online mental assessment and training programs, and other technology-based sport applications, coaches and athletes are flooded with new products and often want guidance for separating out the high and low-value offerings. (Knowing time, money, and energy resources are limited in a busy season, and my passion for sleep as a recovery tool, I often respond to coaches that the research literature says you should bet on your athletes getting more - or higher quality - sleep rather than using a certain brain training device for cognitive, mood and physical improvements that can lead to athletic performance gains.) I`ve developed a guide specifically for brain training products, and hope that it can provide a structure for coaches as they consider technology decisions. The Psychophysiology Training Lab (aka the Mind-Body Training Center) at the Colorado Springs Olympic Training Center has medical-grade technology for assessing and training brain waves. Looking at brain waves allows the athlete to see the objective aspect of the mental skills that we are training. Recently, a number of consumer brain training products have hit the market. They are well-marketed, often directly to athletes, and increasingly affordable as competition forces down the purchase and/or subscription price.